Pengaruh Tingkat Penerimaan Teknologi E-Wallet Terhadap Perilaku Konsumtif Generasi Milenial Kota Bandung - Adiba Nuha Rabbani; Ria Haryatiningsih (UNISBA Press, 2024)
Abstract. The digital era has had an impact on society, encouraging the utilization of technology for financial transactions, especially among the millennial generation, which is more influenced by technological advancements and responsive to environmental changes. One prevalent technology in use today is E-Wallet technology, which is a part of financial technology (fintech) as a company providing financial services with a modern technological touch. Financial Technology (fintech) has evolved with the lifestyle of the community, involving technology in daily activities. The analytical method used in this research is quantitative with a descriptive approach, utilizing SmartPLS 3.0 as the tool. Sample collection technique involves purposive sampling, with 100 respondents from the millennial generation in Bandung who are users of E-Wallet technology. The measurement scale used is the Likert scale. Based on the questionnaire data processing, conclusions can be drawn regarding Perceived Ease of Use, Perceived Usefulness, Attitude Toward Using, Behavioral Intention, and Actual Use, all of which exhibit strong perceptions indicated by the intervals of strongly agree and agree. Additionally, there is a significant influence between technology acceptance and the variable of consumptive behavior, as evidenced by a T-Statistic value of 9.180. However, both variables only demonstrate a moderate relationship, as indicated by an R-Square value of 28.5%, meaning that the remaining 72.5% is influenced by other variables not covered in this study. Abstrak. Era digital memberikan dampak pada masyarakat untuk memanfaatkan teknologi sebagai transaksi keuangan terutama pada generasi milenial yang lebih terpengaruh pada perkembangan teknologi dan reaktif pada perubahan lingkungan. Salah satu teknologi yang marak dipakai saat ini ialah teknologi E-Wallet yang merupakan bagian dari financial technology (fintech) sebagai perusahaan penyedia jasa keuangan dengan sentuhan teknologi modern. Financial Technology (fintech) berkembang dengan adanya gaya hidup masyarakat yang melibatkan teknologi pada aktivitas sehari-hari. Metode analisis dalam penelitian ini menggunakan metode kuantitatif dengan pendekatan deskriptif serta menggunakan alat SmartPLS 3.0. Teknik pengumpulan sampel menggunakan purposive sampling atau sampel bertujuan, yaitu sebanyak 100 responden generasi milenial Kota Bandung pengguna teknologi E-Wallet. Skala pengukuran yang dipakai ialah dengan skala likert. Berdasarkan pengolahan data kuesioner maka dapat diperoleh kesimpulan yaitu pada Perceived Ease of Use, Perceived Usefulness, Attitude Toward Using, Behavioral Intention, dan Actual Use memiliki persepsi kuat yang ditunjukkan pada interval sangat setuju dan setuju. Selain itu, terdapat pengaruh yang signifikan antara penerimaan teknologi terhadap variabel perilaku konsumtif yang ditandai dengan nilai T-Statistic sebesar 9,180. Namun, pada kedua variabel tersebut hanya menujunjukkan hubungan moderat yang ditandai dengan nilai R-Square sebesar 28,5 pesen, sehingga besaran nilai 72,5 persen lainnya dipengaruhi oleh variabel diluat penelitian ini.